Can the Combined Use of the Mirid Predator Nesidiocoris tenuis and a Braconid Larval Endoparasitoid Dolichogenidea gelechiidivoris Improve the Biological Control of Tuta absoluta? - Pascal Osa Aigbedion-Atalor (MDPI AG, 2021)
The koinobiont solitary larval endoparasitoid Dolichogenidea gelechiidivoris (Marsh) (Syn.: Apanteles gelechiidivoris) (Hymenoptera: Braconidae) and the predatory bug Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae) are important natural enemies of Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae), a serious pest of tomato. Although N. tenuis preferentially feeds on T.absoluta eggs, it is also recorded as a predator of first and second instar larval stages. Dolichogenidea gelechiidivoris preferentially seeks these early larval stages of T. absoluta for oviposition. The occurrence of intraguild predation between N. tenuis and D. gelechiidivoris and the consequences on the oviposition performance of D. gelechiidivoris were investigated in the laboratory. Regardless of the manner of introduction (i.e., the sequence of combinations with D. gelechiidivoris) or density (i.e., number of N. tenuis combined with D. gelechiidivoris), the presence of N. tenuis did not affect the oviposition performance of D. gelechiidivoris or the parasitoid’s progeny. Combination assays revealed that the efficacy of the combined use of N. tenuis and D. gelechiidivoris in controlling T. absoluta populations was significantly higher than that of either natural enemy alone. Our results highlight the potential of combining mirid predators and koinobiont larval endoparasitoids to control T. absoluta. The findings further contribute to data supporting the release of D. gelechiidivoris in tomato agroecosystems for the control of T. absoluta in Africa, where N. tenuis is widespread and abundant.